KEMISKINAN DI KAWASAN PINGGIRAN HUTAN : Studi Kasus di Kawasan Pinggiran Hutan Pakuncen Banyumas - Watemin Watemin; Sulistyani Budiningsih (Universitas Muhammadiyah Purwokerto, 2008)
This research was to knowing at poverty rate of farmer’s household in marginal community of forestry region. That was performanced at the marginal forestry in Pekuncen Sub District, Banyumas Regency by descriptive method. Data was taken by simple random sampling amount of 10 percent from population on two villages in marginal forestry. It was continued by Foster – Greer – Thorbecke (FGT). The result showed that poverty rate for Head Count Index of 0.6054, Poverty Gap Index of 0.3011, and Distributionally Sensitive Index of 0.1889.